The Inhibition of Cyanobacteria Spirulina Extract on S. Mutans Biofilm as an Ingredient in Mouthwash - Henu Sumekar; Linda Rochyani; Istien Wardani (Denta Journal Kedokteran Gigi, 2024)
Background: The main cause of dental caries is Streptococcus mutans (S. mutans), to suppress the growth of cariogenic bacteria can be done by using mouthwash containing antibacterial ingredients such as chlorhexidine. Cyanobacteria spirulina extract contains compounds that have secondary metabolites which act as antibacterial and antioxidant including tannins, flavonoids, saponins and terpenoids. Objective: This study aimed to find out he inhibition of Cyanobacteria spirulina against S. mutans biofilm. Materials and Methods: The research sample consisted of 6 groups. Group K(-) was the S. mutans biofilm with aquadest, K(+) was Chlorhexidine 0.2% and four treatment groups (P1, P2, P3, P4), which were Cyanobacteria spirulina extract with a concentration of 60 , 70, 80 and 90 mg/ml. The sample was applied to a well microtiter plate, then incubated overnight at 37°C for 1 x 24 hours, then painted with 0.1% crystal violet. After that, it was rinsed with sterile distilled water, then given 0.2 mL of Tween 80 concentration of 2% and measured Optical Density with an ELISA Reader with a wavelength of 570 nm, then biofilm inhibition percentage as calculated. Results: The mean value of the percentage of S. mutans biofilm inhibition in group K(+): -131,694(SD 10,758) ; P1: -12,234(SD 2,402) ; P2: 11,076(SD 6,387) ; P3: 19.7020(SD 11,670) ; P4: 40,214(12,057) there were significant differences between P2 and P4 also between P3 and P4. Conclusion: Cyanobacteria spirulina at concentrations of 70, 80 and 90 mg/ml had S. mutans biofilm inhibition, while Chlorhexidine 0.2% and Cyanobacteria spirulina 60 mg/ml did not.